2016
DOI: 10.1007/s11060-016-2327-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of p-Mnk1, p-eIF4E and p-p70S6K proteins are associated with tumor recurrence and poor prognosis in astrocytomas

Abstract: Malignant astrocytomas are able to invade neighboring and distant areas of the normal brain. Signaling pathway alterations play important role in the development of astrocytomas. Deregulation of eukaryotic translation initiation factor 4E (eIF4E) by MAP kinase-interacting kinases (Mnk) on Ser-209 directly or PI3K/mTOR/S6K pathway indirectly has a critical effect on promoting cellular proliferation, malignant transformation and metastasis. We examined and analyzed the correlation between expression of p-Mnk1, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…In our study, we found that NSCLC patients had high positive expression of p-mTOR and p-eIF4E proteins, which supports our previous findings in NPC and astrocytomas [38][39][40]. Expression of p-Akt was mainly localized in cytoplasm, a few in the nuclear or membrane, which indicates that p-Akt may play an important role in the cytoplasm and nucleus/ Overexpression of p-Akt, p-mTOR and p-eIF4E proteins in NSCLC membrane, thereby activating its downstream signaling pathway and promoting the development of tumors.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found that NSCLC patients had high positive expression of p-mTOR and p-eIF4E proteins, which supports our previous findings in NPC and astrocytomas [38][39][40]. Expression of p-Akt was mainly localized in cytoplasm, a few in the nuclear or membrane, which indicates that p-Akt may play an important role in the cytoplasm and nucleus/ Overexpression of p-Akt, p-mTOR and p-eIF4E proteins in NSCLC membrane, thereby activating its downstream signaling pathway and promoting the development of tumors.…”
Section: Discussionsupporting
confidence: 92%
“…Both MNK1 and MNK2 mRNAs have been found ubiquitously expressed in a variety of tissues by northern blot analysis. Fan et al recently observed a considerably higher percentage of active phospho-MNK in astrocytomas, further endorsing the role of active MNK in cancer [47,52]. High levels of phosphorylated MNK1 are also observed in HER-2 positive breast cancer and in glioblastoma multiforme primary tumors.…”
Section: Mapk-interacting Kinasesmentioning
confidence: 91%
“…3 and 4) [22]. Other groups have confirmed the prognostic importance of these factors in additional tumor types (Table 1), including colon cancer [61,62], nasopharyngeal carcinoma [63], hepatocellular carcinoma [64], astrocytomas [65], lung cancer [66,67], and melanoma [68]. Importantly, eIF4E is a central regulator of metastatic progression [69][70][71] (Fig.…”
Section: Expression Of Signaling Factors In Human Tumorsmentioning
confidence: 80%